Computational Intelligence In Digital Forensics: Forensic Investigation And Applications - Azah Kamilah, Muda; Yun-Huoy, C.; Abraham, Ajith; Srihari, Sargur N. (Springer, 2014)
The Series "Studies in Computational Intelligence" publishes new development and advances in the various areas of computational intelligence - quickly and with a high quality. The intent is to cover the theory, applications, and design methods of computational intelligence, as embedded in the fields of engineering, computer science, physics and life science, as well as the methodologies behind them. The series contains monographs, lecture notes and edited volumes in computational intelligence spanning the areas of neural networks, connectionist systems, genetic algorithms, evolutionary computation, artificial intelligence, cellular automata, self-organizing systems, soft computing, fuzzy systems, and hybrid intelligent systems. Of particular value to both the contributors and the readership are the short publication timeframe and the world-wide distribution, which enable both wide and rapid dissemination of research output.